Advancements of mass spectrometry in biomedical research - Darie, Costel C.; Woods, Alisa G. (Advances in Experimental Medicine and Biology, 2014)
This volume explores the use of mass spectrometry for biomedical applications. Chapters focus on specific therapeutic areas such as oncology, infectious disease and psychiatry. Additional chapters focus on methodology as well as new technologies and instrumentation. This volume provides readers with a comprehensive and informative manual that will allow them to appreciate mass spectrometry and proteomic research but also to initiate and improve their own work. Thus the book acts as a technical guide but also a conceptual guide to the newest information in this exciting field. Mass spectrometry is the central tool used in proteomic research today and is rapidly becoming indispensable to the biomedical scientist. With the completion of the human genome project and the genomic revolution, the proteomic revolution has followed closely behind. Understanding the human proteome has become critical to basic and clinical biomedical research and holds the promise of providing comprehensive understanding of human physiological processes. In addition, proteomics and mass spectrometry are bringing unprecedented biomarker discovery and are helping to personalize medicine.